The power of reflection in teacher education and professional development : strategies for in-depth teacher learning - Korthagen, Fred A. J., 1949-; Nuijten, Ellen E. (2022)
"Based on years of extensive research on teacher development, this book offers a practical introduction to the concept of teacher reflection, demonstrating how current and future teachers can engage with the concept of reflection and learn from their teaching, learning, and classroom experiences in a systematic and inspiring way. Providing practical models and guidelines for use in the classroom, renowned teacher educators Fred A. J. Korthagen and Ellen E. Nuijten outline various levels of reflection and illustrate how a deeper form of reflection - 'core reflection' - enhances awareness of professional identity, supports the dismantling of inner obstacles that prevent social justice, and empowers diverse student populations. The authors demonstrate how a trajectory for learning can be designed to develop key competencies, and particular discussion is focused on the roles of university- and school-based teacher educators in supporting teachers' motivation for self-directed reflection. Featuring a variety of tools effective for professional growth, this unique book demystifies the area of teacher reflection, helping to provide concrete and inspiring examples for how to strengthen professional identity based on everyday challenges faced by practitioners. The Power of Reflection in Teacher Education is therefore an essential guide for students, in-service teachers, and teacher educators alike. Fred A. J. Korthagen is Professor Emeritus at Utrecht University and Director of the Korthagen Institute for Professional Development in the Netherlands. Ellen E. Nuijten has a master's degree in Human and Organizational Behavior. She is a senior personal coach and team coach, specializing in strength-based reflection and the psychological capital of individuals and teams"--
Introduction: An Exploration of the Concept of Reflection -- Working with the Reflection Model -- Supporting Reflection through Coaching -- Reflection in Peer Groups -- Core Reflection -- Structures and Instruments for Promoting Reflection -- The Promotion of Reflection in Teacher Education.
Keywords: Reflective teaching; Reflective learning; Holistic education; Motivation in education; EDUCATION / Professional Development